Epidemiology and diagnostic challenges of fever of unknown origin (FUO) among adults: A multicenter retrospective study in Northern Italy - Alessandra Mistral De Pascali; Ludovica Ingletto; Arianna Succi; Martina Brandolini; Laura Dionisi; Claudia Colosimo; Giulia Gatti; Giorgio Dirani; Silvia Zannoli; Valeria Frassineti; Giulia Silvestrini; Carlo Biagetti; et al. (Journal of Infection and Public Health, 2025)
Background: Fever of Unknown Origin (FUO) is broadly defined as a fever with an unidentified cause despite a minimum set of diagnostic investigations. The variability of FUO etiologies across geographic areas, age groups, and decades makes diagnosis challenging and complicates the adoption of a standardized diagnostic approach. Global warming and changing interactions between humans, animals, and the environment are contributing to the emergence and re-emergence of zoonotic infections. Emerging Vector-Borne Disease (VBD) pathogens circulate in Northern Italy, but their prevalence and impact on febrile illnesses remain poorly understood. This study investigated FUO epidemiology, diagnosis, and treatment in three hospitals in Emilia-Romagna (northeastern Italy). Methods: The medical records from 652 patients who were discharged with the International Classification of Diseases, Ninth Revision (ICD-9) codes “780.6 Fever of unknown origin” and “087.9 Relapsing fever, unspecified” between January 2017 and December 2023 were analysed. Results: Among patients discharged with FUO between 2017 and 2023, the mean age was 58 years, and 45 % older than 65 years. Comorbidities were present in 75 %, and 26 % had active cancer. A diagnostic hypothesis was present in 32 % of cases. Diagnostic tests were mainly laboratory-based; 5.9 % had confirmed infections. Antibiotics were used in 62 % of patients mostly penicillin/beta-lactamase inhibitors. FUO discharges peaked in summer. Conclusion: Active hospital-based surveillance are crucial to deepen our current understanding on FUO epidemiology and possible contribution of VBD pathogens while refining the use of antibiotics in the clinical practice.